Research Methodology of Takhrij Hadith - Annisa Mawaddah; Sardianto; Rahman (Penerbit Hellow Pustaka, 2025)
This study aims to answer the urgent need to assess the validity of the Prophet's hadith which is often used as the second source of Islamic law after the Qur'an. In scientific reality, many hadith are used without tracing the source, sanad, or assessing its quality. Therefore, this study is important to provide a systematic understanding of the takhrij hadith method. This article is categorized as a research article with a qualitative approach and uses a literature study of various primary and secondary sources, including books by Mahmud al-Tahhan and classical hadith scholars. This study reviews five main methods of takhrij hadith, namely based on the initial wording of the hadith, keywords of the matan, the first narrator, the theme of the hadith, and based on the quality status of the hadith. The results of the study show that each method has its own relevance and function that can be selected according to the needs, linguistic abilities of the researcher, and the structure of the book used. Takhrij hadith is proven to be not only a technical process of tracing, but is a methodological approach that requires precision, the ability to analyze sanad-matan, and mastery of hadith books. The conclusion of this study confirms that mastery of takhrij science is essential in maintaining the authenticity of Islamic teaching sources, especially in the academic and fatwa context. In the future, the development of a digital takhrij system and the integration of technology-based hadith indexes are very potential directions to facilitate this process on a global scale.